Lithuanian Folklore Published in Wisła: Bibliographic Inventory (1888–1899) - Adamaitytė, Agata; Rutkovska, Kristina (Tautosakos darbai, 2018)
The journal Wisła published in Poland in 1887–1905 played an important role both in the development of European folklore research and in collecting of factographic materials. Wisła also published some Lithuanian folklore and its research. The majority of publications related to the traditional Lithuanian culture was included into the volumes published in 1888–1899, when the renowned Polish ethnographer, dialectologist, lexicographer and comparative linguist Jan Karłowicz was the editor of the journal. He had earlier personally organized folklore collection in Lithuania, acquired contributors there and compiled a special guide for collecting “mythology” in Lithuania. The journal received articles and data collections from brothers Antanas and Jonas Juška, Juozas Kybartas, Jonas Vitartas, Antanas Miežinskis, Tadas Daugirdas, Bruno Korotyński and Ludwik Korotyński, Rafał Lubicz, Alfred Römer, Mečislovas Davainis-Silvestraitis, etc. The journal published in total about 200 articles and miscellaneous information based on the data from Lithuania. Here we present the bibliographic inventory of various articles and information, bibliographic references and other items important for the Lithuanian folklore research and published in Wisła from 1888 to 1899. Compilation of the inventory follows the structure of the journal, which corresponded to the pattern adopted also by other ethnographic European journals of the time. The journal comprised three chapters. The first was entitled “Articles” (Artykuły) and contained works based on scholarly analysis. The second chapter was called “Bibliographic information” (Bibljograficzno-informacyjny) and reviewed and evaluated publications of Polish and foreign folklore. From 1888 onwards, every book of some scholarly merit received its review in the journal; thus, information on research conducted in other countries could rapidly reach the scholars. The third chapter was entitled “Search” (Poszukiwania) and published materials for scholarly research.